Under an ionized sky : from chemtrails to space fence lockdown - Freeland, Elana (Feral House, 2018)
It is difficult to believe that our planet has been weaponized before our very eyes, but that is exactly what has happened. First, we were seduced by the convenience of a wireless world; then, atmospheric weather experimentation in the guise of carbons "climate change" converted the air we breathe into an antenna. Now, the geo-engineering we've been subjected to for two decades is being normalized as the "Star Wars" Space Fence rises around and within us. Is this the Space Age we were promised?